The Civil War soldier and the press
1 online resource
Keywords: "The Civil War Soldier and the Press examines how the press powerfully shaped the nation's understanding and memory of the common soldier, setting the stage for today's continuing debates about the Civil War and its legacy. Both scholarly and approachable, this book is an enriching resource for undergraduate and graduate courses in Civil War history, American History, journalism, and mass communication history"--